Immigrant rights and social movements. Issue 8 (11th July 2018) - Mora, Maria De Jesus; Rodriguez, Rodolfo; Zermeño, Alejandro; Almeida, Paul
Abstract: The disciplinary fields of immigration and social movements have largely developed as two distinct subareas of sociology. Scholars contend that immigrant rights, compared to other movements, have been given less attention in social movement research. Studies of immigrant‐based movements in recent decades have reached a stage whereby we can now assess how immigrant movement scholarship informs the general social movement literature in several areas. In this article, we show the contributions of empirical studies of immigrant movements in four primary arenas of social movement scholarship: (a) emergence; (b) participation; (c) framing; and (d) outcomes. Contemporary immigrant struggles offer social movement scholarship opportunities to incorporate these campaigns and enhance current theories and concepts as earlier protest waves advanced studies of collective action.